A Teaching Strategies for Students with ADHD in Inclusive Elementary EFL Classrooms: A Qualitative Case Study from an Islamic School in Indonesia - Nadila Adelia Putri; Didik Santoso (Faculty of Education and Teacher Training of UIN Palopo, 2026)
Teaching English to students with Attention Deficit Hyperactivity Disorder (ADHD) in inclusive classrooms requires appropriate strategies to address their attention, behavioral, and language-learning challenges. However, studies focusing specifically on English teaching strategies for ADHD students at the elementary level remain limited, particularly in inclusive Islamic school contexts. This study aimed to explore the strategies used by an English teacher in teaching English to students with ADHD at an inclusive Islamic elementary school in Medan, Indonesia. This study employed a qualitative case study design involving one female English teacher, approximately 28 years old, who had four years of experience teaching English to three male students diagnosed with ADHD at the school. Data were collected through semi-structured interviews and lesson plan analysis and analyzed using Braun and Clarke’s (2006) thematic analysis. Based on the analysis of teacher interviews and lesson plans, the findings identified thirteen teaching strategies: expressing greetings in english, managing students attention, providing ice breaking, notifying the learning objectives, writing the lesson topic on the board, explaining the meaning of the lesson topic, giving example, repeating example together, giving exercise, giving feedback, giving assignment, lesson review, and giving rewards. These findings highlight that structured, visual, active, and reinforcement-based strategies play an important role in supporting English learning for students with ADHD. This study contributes to the literature on inclusive English teaching by providing practical evidence of how instructional strategies are systematically planned and implemented in an underexplored Islamic elementary school context.